PROJECT-BASED IMPLEMENTATION OF E-LEARNING IN ENGLISH LANGUAGE TEACHING: DESIGN, IMPLEMENTATION, AND EVALUATION (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The integration of digital technologies into higher education has created new opportunities for improving the quality and flexibility of English language instruction. However, the effectiveness of e-learning largely depends on systematic planning and management rather than the simple use of technological tools. This study aims to examine the design, implementation, and evaluation of an e-learning system for English language teaching using a project-based approach. The research was conducted at a private higher education institution in Tashkent and involved 100 undergraduate students at the B1 level. The e-learning course was developed and managed using the ADDIE instructional design model and implemented as a supplementary component to traditional face-to-face instruction over an eight-week period. Data were collected through pre-test and post-test results, platform activity records, course completion statistics, and a student satisfaction survey.